Educating Cities and Cultural Heritage: theoretical approach - Gabriel, Maria Helena; Vieira, Ana Paula de Castro; Castral, Paulo César (National Journal of City Management, 2022)
The proposal is to review the concept of Educating City, in order to better understand the cities that have this seal of approval and relate it to the actions inherent to the process of defining and safeguarding the Cultural Heritage, establishing a theoretical approach between both concepts. The aim is to discuss the approaches that enhance the dialogue between the different social agents in the solution of problems characteristic of living in cities. To do so, a bibliographical review will be made, approaching both the recent discussions on Cultural Heritage and the beginning of the discussions that raised the idea of " educative city" to become the Educating City concept. In this sense, the Charter of Educating Cities defines points that consider important documents such as the Declaration of Human Rights, among others. Finally, it is verified how the experiences in the Educating City can contribute to the preservation of the Cultural Heritage defined by social groups and communities that identify themselves with this heritage and how the conceptual meeting between Educating City and Cultural Heritage can be contemplated in the practices of Heritage Education.